THE DENOTATIONAL SEMANTICS OF PROCEDURAL PROGRAMS (the solution to the problem of variables’ number minimization) - Aghasian, M. M. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2002)
In this article an algorithm is described, which brings every program, written in procedural language, to conformity with such a system of functional equations, that defines its denotational semantics and in each equation the number of variables is minimal. The algorithm uses the mathematical model, for which the existence of the least element is proved.